Internet censorship detected in Cambodia (Cambodia) - Voidly (2026)
CRITICAL severity censorship detected in Cambodia. Confidence: 65%. Data sourced from CensoredPlanet.
Censorship Incident ID: KH-2026-0088
Keywords: censorship; KH; censorship; critical